2022
DOI: 10.1073/pnas.2204581119
|View full text |Cite
|
Sign up to set email alerts
|

Functionally linked potassium channel activity in cerebral endothelial and smooth muscle cells is compromised in Alzheimer’s disease

Abstract: The brain microcirculation is increasingly viewed as a potential target for disease-modifying drugs in the treatment of Alzheimer’s disease patients, reflecting a growing appreciation of evidence that cerebral blood flow is compromised in such patients. However, the pathogenic mechanisms in brain resistance arteries underlying blood flow defects have not yet been elucidated. Here we probed the roles of principal vasodilatory pathways in cerebral arteries using the APP23 mouse model of Alzheimer’s disease, in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…We examined K IR 2 channel activation using physiologically relevant increases in [K + ] E for vasodilation (up to 15 mmol/L). 38 Further, as compromised regulation of endothelial K IR 2 channels occurs in the brain during AD, [13][14][15][16] we pursued this work in aging 3xTg-AD mice. As consistent with previous findings, 7,10 we found that electrical conduction remains equally efficacious regardless of charge polarity (for hyperpolarization or depolarization) and axial direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined K IR 2 channel activation using physiologically relevant increases in [K + ] E for vasodilation (up to 15 mmol/L). 38 Further, as compromised regulation of endothelial K IR 2 channels occurs in the brain during AD, [13][14][15][16] we pursued this work in aging 3xTg-AD mice. As consistent with previous findings, 7,10 we found that electrical conduction remains equally efficacious regardless of charge polarity (for hyperpolarization or depolarization) and axial direction.…”
Section: Discussionmentioning
confidence: 99%
“…Using a dual intracellular electrode method in endothelial tubes of mouse posterior cerebral arteries, 10 the current study addressed (1) bidirectional efficacy and (2) potential K IR 2 channel regulation of electrical conduction. Further, in light of recent data for the impact of Alzheimer's disease (AD) on overall vascular health, 11,12 and specifically on endothelial K IR 2 channels, [13][14][15][16] our study model of choice entailed young Pre-AD (1-3 months) and aged AD (13-18 months) 3xTg-AD animals. 17,18 With a normal reference of 5 mmol/L for extracellular potassium ([K + ] E ) 3,19,20 elevated [K + ] E as 8 to 15 mmol/L activated K IR 2 channels.…”
mentioning
confidence: 99%
“…Nonlinear waves are physically and currently interesting [1][2][3]. Physical studies on the pulse waves in the human arteries have started from the ancient times until the present, while recent theoretical efforts have been focused on the probes for nonlinear pulse waves in the variable-radius arteries [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Background Around Us and Our Considerationmentioning
confidence: 99%
“…For simplicity, derivations are elided 8. The word 'quasi' implies that there still exist ρ 1 (t), ρ 2 (t) and ρ 3 (t), beyond the travelling-wave format.…”
mentioning
confidence: 99%
“…hypertension, Osol & Halpern, 1985) or not (e.g. neurodegeneration, Taylor et al, 2022). The impetus for today's vascular physiologist is the promise of identifying additional myogenic control points that have the potential to restore normal blood flow in these conditions.…”
mentioning
confidence: 99%